Evaluation of Medical Waste Management in Al-Wahda Therapeutic Hospital in Derna City: A Study in Medical Geography - Marei Rafallah Saad Al-Fakhakhri (Journal of Libyan Academy Bani Walid, 2025)
This study seeks to evaluate waste management in Al-Wahda Therapeutic Hospital in Derna City in terms of sorting, collection, transportation, storage and final disposal, in addition to knowing the amount of medical waste produced by the hospital. The study relied on several methods to collect information, including writing notes during field work as well as the questionnaire. The results showed that the general average of medical waste production was 1.6 kg/bed/day, then the amount of medical waste was determined for each department of the hospital, and the highest value was in the internal medicine department with an average of 42 kg/day, and did not exceed 3.2 kg/day in the ENT department, and also the sorting between hazardous and non-hazardous medical waste is not done in most departments, through the field study, it became clear to the researcher that the sorting operations include sharp tools such as needles, scalpels, etc. The study also showed through the interview conducted with one of the hospital staff, it became clear to the researcher that there is no warehouse dedicated to storing hazardous medical waste, as medical waste is not classified, but is collected within the departments and transferred directly to the collection yard located within the hospital building fence, and thus this method of storage is not in accordance with the standards of the World Health Organization, and the method used in treating hazardous medical waste is (chopping and sterilization), as there is a grinder that is operated four times a day and the operating capacity of the grinder is about 35 kilograms, this method is characterized by It is safe for the surrounding environment, low in cost, and does not require a large workforce. The most important disadvantage of this method is that it is not suitable for treating pathological and biological waste. The results of the questionnaire also showed that 69.1% of the total sample of the study are not qualified for the waste classification process, as they did not receive any educational courses or workshops in dealing with hazardous waste resulting from the hospital, while we find that about 30.9% of the sample of the study, which is 68 individuals, are the only ones who have courses and experience in this field and have high efficiency in dealing with hazardous medical waste.